My name is Lucy Barton [compact disc, unabridged] : a novel - Strout, Elizabeth (Books on Tape ; Random House Audio, 2016)
Lucy Barton is recovering slowly from what should have been a simple operation. Her mother, to whom she hasn't spoken for many years, comes to see her. Gentle gossip about people from Lucy's childhood in Amgash, Illinois, seems to reconnect them, but just below the surface lay the tension and longing that have informed every aspect of Lucy's life: her escape from her troubled family, her desire to become a writer, her marriage, her love for her two daughters. Knitting this powerful narrative together is the brilliant storytelling voice of Lucy herself: keenly observant, deeply human, and truly unforgettable.